Manajemen Terpadu Bronkopneumonia dan Suspek Penyakit Jantung Bawaan pada Bayi dengan Sindrom Down - Kamila Nastiti; Shinta Nareswari (CV. Jasa Sukses Abadi, 2026)
Bronchopneumonia is a major cause of morbidity and mortality in children under 5 years of age, particularly in developing countries. Infants with Down syndrome are known to have a higher susceptibility and risk of lower respiratory tract infections, including bronchopneumonia. We report the case of a 3-month-old female infant who presented to the Emergency Department of Dr. H. Abdul Moeloek Regional Hospital, Bandar Lampung with shortness of breath accompanied by a productive cough and fever for 7 days prior to admission. Physical examination revealed tachypnea (respiratory rate 56 breaths/min), tachycardia (heart rate 168 beats/min), body temperature 39.0°C, and an oxygen saturation of 91% on room air. Lung auscultation revealed bilateral rhonchi and wheezing. In addition, facial dysmorphic features typical of down syndrome and a continuous murmur in the left subclavicular area were found. Chest radiography demonstrated diffuse peribronchial infiltrates with bilateral patchy opacities, suggestive of bronchopneumonia. The patient was diagnosed with bronchopneumonia, down syndrome, and patent ductus arteriosus. Management included supportive therapy, intravenous antibiotics (ampicillin–sulbactam and gentamicin), and diuretics (furosemide). The patient’s clinical condition gradually improved, and the patient was discharged in good condition. This case highlights the increased susceptibility of infants with down syndrome to bronchopneumonia, including the potential presence of congenital heart disease as a comorbidity that may worsen the patient's clinical condition. A comprehensive management approach, including pharmacological and nonpharmacological therapies, as well as early evaluation of comorbidities, is crucial to improve patient outcomes.